2001
DOI: 10.1055/s-2001-19515
|View full text |Cite
|
Sign up to set email alerts
|

Prognostische Bedeutung einer Diabeteserkrankung beim Endometriumkarzinom

Abstract: Our results show a correlation between Diabetes mellitus and adverse prognostic factors witch affects by the rate of lymphonode spread and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…Endometrial Carcinoma is often associated with medical disorders such as hyperten-sion, diabetes mellitus, obesity, PCOS, and infertility 17,18. Steiner et al,19 found 21.8% of…”
mentioning
confidence: 97%
“…Endometrial Carcinoma is often associated with medical disorders such as hyperten-sion, diabetes mellitus, obesity, PCOS, and infertility 17,18. Steiner et al,19 found 21.8% of…”
mentioning
confidence: 97%